Thermal and Mechanical Analysis of Plywood Boards Thermally Enhanced with Phase Change Materials - Vasco-Calle, D (Institute of Physics Publishing, 2020)
Adding Phase Change Materials (PCM) in construction elements and materials increase their thermal mass, which may reduce temperature variation of indoor environment and improve thermal comfort of occupants. The present paper aims to study the thermal and mechanical impacts of embedding microencapsulated PCM in the adhesive of plywood boards. Mechanical properties of samples are measured using a standardized bending test; thermal mass is estimated with a homemade experimental setup based on a heated bed and two thermocouples. Tests were carried out on three different samples: a reference sample without PCM, a second sample with adhesive containing 25% of PCM, and a third sample with 30% of PCM. The most relevant results from the study showed that the mechanical properties of plywood boards were not significantly affected by the PCM, and the thermal mass was improved up to 19% on a variation of 30C. © 2020 Published under licence by IOP Publishing Ltd.